Peran Pemasaran Global dalam Mendorong Kemajuan Ekonomi Indonesia - Elia Cahyani; Tazkiyyah Nururrohmah; Mohamad Zein Saleh (Pusat Riset dan Inovasi Nasional, 2023)
Global competition requires Indonesian companies to continue to innovate and improve production efficiency. This will help improve the competitiveness of Indonesian products in the domestic and international markets. The purpose of this study is to analyse the role of global marketing in driving Indonesia's economic progress. This research method is descriptive research method. The data source of this research is secondary data. The result of this study is that global marketing has a significant impact on the development of the Indonesian economy. By expanding market coverage, increasing exports, and introducing Indonesian brands to the global market, Indonesia can enjoy benefits such as increased income and transmission of technology and knowledge between international markets. Therefore, businesses in Indonesia should consider global marketing principles to improve the country's competitiveness and economic growth.